The association between the Dietary Inflammatory Index and breast cancer risk: an updated systematic review and meta-analysis - Wang, Chaoyang; Zhou, Qian; Chen, Liang; Zhai, Chao (Frontiers in Nutrition, 2026)
ObjectiveThis meta-analysis aimed to clarify the relationship between the Dietary Inflammatory Index (DII) and the risk of breast cancer (BC), thereby providing an evidence-based foundation for the primary prevention and secondary management of BC.MethodsA systematic search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library for relevant studies published up to September 30, 2025. Observational studies (case-control and cohort) reporting effect estimates (OR/HR with 95% CI) for the association of DII/E-DII with BC risk or prognostic outcomes were included. Effect sizes were pooled using a random-effects model. Heterogeneity was assessed, and subgroup analyses along with publication bias evaluation were performed.ResultsNineteen studies (14 case-control, 5 cohort) were included. Case-control studies demonstrated a significant positive association between a higher DII and increased BC risk (pooled OR = 1.91, 95% CI: 1.50–2.42), a trend consistently observed in both premenopausal and postmenopausal women. Cohort studies further confirmed that elevated DII scores were associated with a higher risk of BC (pooled HR = 1.08, 95% CI: 1.01–1.15). Each one-unit increase in the DII was correlated with an approximate 2% rise in BC risk. Moderate heterogeneity was detected among the studies, primarily attributable to variations in DII categorization methods and population characteristics.ConclusionThe current evidence suggests that the DII is associated with BC risk, with pro-inflammatory dietary patterns linked to a higher risk of breast cancer. Promoting anti-inflammatory dietary habits, characterized by abundant consumption of fruits, vegetables, whole grains, and healthy fats, holds substantial public health importance for the prevention and management of BC.